Ensemble-based Classification Models for Predicting Post-Operative Mortality Risk in Coronary Artery Disease. (2018) - Brobbey, Anita; Faris, Peter; Nettel-Aguirre, Alberto; Williamson, Tyler; Wiebe, Samuel; Peng, Mingkai; Quan, Hude; Sajobi, Tolulope T
No abstract available